Free Radical Scavenging Activity of Ethanolic Leaves Extract and Its Different Solvent Fractions of Piper betle L. In Vitro - Risdian, Chandra; Widowati, Wahyu; Mozef, Tjandrawati; Wargaseti, Teresa Liliana; Khiong, Khie (Indonesian Journal of Cancer Chemoprevention, 2011)
Various diseases including cancer and cardiovascular diseasesare induced by free radicals via lipid peroxidation, protein peroxidation, DNA damage, and cellular degeneration in thecells.Piper betle L.,commonly called betel,belongs to thePiperaceae family.It originated from South and South Eas tAsia,and has been used as a traditional medicine by people theredue to its medicinal properties.In the present study, free radicalscavenging activity of ethanolic leaves extract of Piper betle L.together with its different solvent fractions(hexane,ethylacetate,butanol,and water)were evaluated by DPPH freeradical scavenging assay.The ethanolic extract and the ethylacetate fraction had shown very significant DPPH (1,1)diphenyl)2)picryl)hydrazyl) radical scavenging activitycompared to the other fractions.In DPPH free radical scavengingassay,the IC50 value of the ethanolic extract and the ethyl acetate fraction were found to be 17.431g/mL and 11.53 1g/mL, respectively. The free radical scavenging activity was assumed due to the total phenolic content.The total phenoliccontent was found to be highest in the ethanol extract(277.68ÃÂµgEGCG/mg)and the ethyl acetate fraction(559.38ÃÂµgEGCG/mg).The results concluded that the ethanolic leaves extract of PiperÃÂ  betle L. and its ethyl acetate fraction have a consider ably freeradical scavenging activity.